Qatari national scholarships: University selectivity and student outcomes - Ramzi Nasser (10099940) (2015)
The scholarship program in Qatar provides aid for students wishing to enroll in “top-ranked” universities around the world by supplying them with tuition, fees, board, and travel. The selectivity (high or low ranking, as determined by international ranking agencies) of the universities implies specific outcomes in terms of graduation and time of study at the university. In this study we attempt to understand how selectivity is related to education functional outcomes. Based on Qatari students enrollment in higher education programs around the world, students were bifurcated into high ranking or low ranking universities and whether they graduated or terminated in relation to specific functional outcome as in achievement (e.g. grade point average) and time of study in a program. A Kruskal-Wallis analysis was conducted using the selectivity of university as an independent variable and graduation status (whether they were terminated or graduated) on student university achievement and time of study. The finding showed the main effects for selectivity, bifurcated into ranked universities (top-1096 universities) and those non-ranked on university achievement. When the selectivity was narrowed by bifurcating students who were enrolled in highly ranked (top-200 universities) and those lower-ranked universities (below the top 200-ranked universities or non-ranked universities), a main and significant statistical difference was found for selectivity on university achievement and time of study. Surprisingly, those in the “top- ranked” universities were more likely to underperform than those in the lower-ranked universities. The findings suggest that students who enroll in high ranking universities were more likely to face difficulty in maintaining the high averages to continue. A greater insight and qualitative approaches is needed to understand Qatari student lower achievement in the top ranking universities around the world. Other Information Published in: Near and Middle Eastern Journal of Research in Education, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/nmejre.2015.3